Donor site morbidity following microvascular fibula transfer - Jesudass, Joyce; Sivakumar, Anoop; Kain, Rakesh (International Surgery Journal, 2020)
Background: The free vascularized fibula has become the first choice of vascularised bone transfer. The advantages of fibula over other microvascular flaps include greater bone length, sufficient pedicle length and size, rich periosteal blood supply, etc. Aim: This study was designed to evaluate the long-term donor site morbidity following microvascular fibula transfer. Methods: This study was conducted over two years, in patients who underwent free fibula flap for various defects which needed a composite osseo-fasciocutaneous flap. They were followed up for one year and the donor site evaluated for complications like edema, pain, anaesthesia, spasm of muscles, Flexor hallucis longus (FHL) contracture, ankle stability and hypertrophic scarring. Results: 28 patients, age ranging 15 to 56 years, of which 22 were male and 6 were female. Total of 7 patients (25%) had complications, of which 6 patients had more than one complication. No patients experienced knee instability, weakness, or decreased range of motion. All patients returned to their normal ambulatory status. Conclusion: Free fibula transfer does have long term donor site complications, but they can be managed conservatively, seldom requiring surgical intervention. However, there are no functional limitations which makes it a feasible option in reconstructing a composite defect.in various literatures.